Exotic medicinal plants from West Vidarbha region - V - Rothe, *S. P. (International Multidisciplinary Research Journal, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; margin-left: 34pt; border-left: medium none; margin-right: 34pt; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Exotics are those plants which are migrated from one region to other region. They are also known as immigrants. Such a plants are now a days considered as a part of forest vegetation because they mixed with the natural floras. About 40% exotics are found in a indigenous floras, their exact time of arrival is different. Some of the plants are migrated from cultivated field or garden due to careless attention. These are considered as naturalized aliens. The present work deals with the report of 26 medicinally important exotics from Vidarbha region.